ANALISIS KEDISIPLINAN KARYAWAN PT. TOTAL JAYA INTERNATIONAL - WILI CHANDRA; HENNY SUHENNY; DIDING KUSNADY; TASIK UTAMA; WONG PONG HAN (LP2MTBM MAKARIOZ, 2019)
In this study, researchers conducted research on employee discipline at PT. Total Jaya International Lubuk Pakam, with theresearch title